Kandungan Protein Kasar dan Serat Kasar Ransum Ternak Itik Mojosari (Anas platyrhynchos) dengan Penambahan Tepung Daun Talas (Colocasia esculenta L): Content of Crude Protein and Crude Fiber Rations Mojosari Ducks (Anas platyrhynchos) with the Addition of Leaf Flour Talas (Colocasia esculenta L.) - Intan Dwi Novieta; Musafir Wana Putera; Munir; Fitriani (Universitas Islam Negeri Alauddin Makassar, 2023)
One alternative feed ingredient that can be used to increase crude protein content and reduce crude fiber content in rations is taro leaves. The purpose of this research is to increase the crude protein content and reduce the crude fiber content in the feed so that it can be used as a nutritional ingredient for animal feed, especially for ducks. The method used in this study was a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments applied were, P0: No treatment, P1: Mixed feed + 1% taro leaf meal, P2: Mixed feed + 2% taro leaf meal, and P3: Mixed feed + 3% taro leaf meal. Based on the results of the study showing that treatment 3 was the best treatment because of the high protein content of 13.79% and the lowest crude fiber content of 11.34%, it can be concluded that the greater the capacity of adding taro leaf flour will increase the crude protein content and reduce Crude fiber content in duck rations.